Combined effects of low-heat cement, expansive agent and shrinkage-reducing admixture on drying shrinkage and cracking of concrete - Lei Fang; Dabao Fu; Qiang Yuan; Song Xu; Dong Zhang; Huangyi Cai; Xiaoqing Zeng; Yong Wang; Jin Zhou (Case Studies in Construction Materials)
The cracking of double-block ballastless track slab concrete has become a critical issue, which can be mitigated through the use of low-heat Portland cement (LC), a MgO-based expansive agent (ME), and a shrinkage-reducing admixture (SR). However, the combined effects of these three components on shrinkage cracking of concrete have not yet been studied. In this paper, the drying shrinkage deformation, cracking risk index (η), and microstructure of ordinary concrete and LC concrete with different contents of ME and SR are systematically studied. The findings indicate that LC decreases the cracking risk of concrete by approximately 38.7 % compared to ordinary Portland cement (PC). By generating expansion crystals and reducing the surface tension of pore solution, both ME and SR can further inhibit the shrinkage of LC, thereby improving the crack resistance of LC-concrete. A significant synergistic shrinkage reduction effect of ME (8 %) and SR (2 %) on LC-concrete is demonstrated, reducing the cracking risk by around 51.04 %. The combined use of SR and ME promotes the formation of more elongated brucite crystals, enhancing particle interaction and improving the cracking resistance of LC. These findings offer essential insights for designing concrete with high crack resistance, ensuring that the cracking risk index remains below the acceptable threshold.